Kontribusi Marāḥ Labīd Syekh Nawawi terhadap Perkembangan Tafsir Nusantara: Analisis Historis dan Intelektual - Salam, Abdul; Nailil Murod, Miftahun; Suwanto, Dwi; Zakaria, Aceng (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Marāḥ Labīd, authored by Shaykh Nawawi al-Bantani, is one of the most influential Qur'anic commentaries produced by a Nusantara scholar and has played a significant role in the development of Qur'anic studies, particularly within Islamic boarding schools (pesantren). However, its epistemological foundations and contribution to the tradition of Nusantara Qur'anic exegesis have not been comprehensively examined. This study aims to analyze the epistemology of interpretation employed by Shaykh Nawawi al-Bantani in Marāḥ Labīd and to explain its contribution to the development of the Nusantara tafsir tradition. This research employs a qualitative descriptive approach using library research. The data were collected from Marāḥ Labīd as the primary source and supported by books, scholarly journal articles, and other relevant literature as secondary sources. The findings indicate that Shaykh Nawawi integrates tafsīr bi al-ma'thūr and tafsīr bi al-ra'y in a balanced manner, reflecting the theological orientation of Ahl al-Sunnah wa al-Jamā'ah and the Shafi'i school. Furthermore, Marāḥ Labīd has significantly contributed to strengthening the intellectual heritage, educational tradition, and development of Nusantara Qur'anic exegesis.